2020
DOI: 10.3889/oamjms.2020.3666
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Nutritional Status in Children Aged 6–24 months in Lamongan Regency, Indonesia

Abstract: BACKGROUND: Family food security and parenting are factors affecting changes in nutritional status related to family care and food availability. AIM: This study aims to analyze the factors affecting nutritional status in children aged 6–24 months in Lamongan Regency, Indonesia. METHODS: The study used cross-sectional data with 191 children aged 6–24 months and their parents, selected by simple random sampling. The data were collected through observations and interviews and used to assess the physic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 17 publications
0
6
0
1
Order By: Relevance
“…The research results show a relationship between regulatory and policy factors and feeding patterns for stunted toddlers. Posyandu can increase knowledge about nutrition and health 20 . Posyandu in the Janti Community Health Center working area is held regularly once a month.…”
Section: Resultsmentioning
confidence: 99%
“…The research results show a relationship between regulatory and policy factors and feeding patterns for stunted toddlers. Posyandu can increase knowledge about nutrition and health 20 . Posyandu in the Janti Community Health Center working area is held regularly once a month.…”
Section: Resultsmentioning
confidence: 99%
“…Research shows a relationship between parenting styles and nutritional status in children under five [12]. Bad parenting impacts the nutritional status of children under five, which is not good.…”
Section: Discussionmentioning
confidence: 99%
“…Score 1 was for the respondents who answered never, score 2 for respondents who answered rarely, score 3 for respondents who answered frequently, and score 4 for respondents who answered very often. The question items consisted of the type of food (1,2,3,4,5), the number of meals given (6, 7, 8, 9, 10), and the schedule of feeding (11,12,13,14,15). After the questionnaire was answered and the results were presented, it was found that the nutrition parenting category was interpreted in the imprecise category <44 % and 45 -100 % correct.…”
Section: Methodsmentioning
confidence: 99%
“…The condition of school-age children and adolescents aged 5-12 years based on the BMI / U index according to the provinces in East Java in 2017 was very thin (3.4 %) and thin (7.5 %). Meanwhile, the prevalence of obesity in school-age children (4.6%) and very obese (3.7 %) are also a part of this (8)(9)(10)(11). This problem is encountered as there are various forms of nutrition problems.…”
Section: Introductionmentioning
confidence: 99%